Tren Positif Kolaborasi AI-Manusia: Survei Guru Musik Indonesia di Era Kurikulum Merdeka - Meyny S. C. Kaunang; Dinar Sri Hartati; Widyata Nikbert Sarayar; Waraney Josua Mongkau; Zelly Jeannie Lombeng; Jans George Mangare; Arie Tulus (Universitas Sultan Ageng Tirtayasa, 2026)
This study analyzes Indonesian music teachers' perceptions of the positive trend in human-AI collaboration in music composition learning during the Merdeka Curriculum era, addressing the local empirical survey research gap absent in prior studies. Employing a mixed-methods approach via systematic literature review (PRISMA-ScR) and Likert-scale survey on 5 music lecturers (N=5), findings reveal an overall mean score of 4.1 (1-5 scale) with 60-80%